Effects of isoflurane on Tei-index of myocardial performance in healthy dogs - Sousa, Marlos Goncalves; Carareto, Roberta; De-Nardi, Andrigo Barboza; Brito, Fablo L. C.; Nunes, Newton; Camacho, Aparecido Antonio (Canadian Vet Med Assoc, 2007)
Recently, the Tei-index, a noninvasive index that combines systolic and diastolic time intervals, has been proposed to assess global cardiac performance. However, the effects of isoflurane on the Tei-index have not been characterized. This study aimed at studying the effects of 1.0 minimal alveolar concentration isoflurane anesthesia on the pre-ejection period (PEP), left ventricular ejection time (LVET), PEP/LVET ratio, isovolumic relaxation time (IVRT), stroke index (SI), cardiac index (CI), heart rate (HR), and the Tei-index in healthy unpremedicated dogs. We observed significant increases in PEP, PEP/LVET ratio, IVRT, and TEI, whose maximal increases obtained throughout the study were 47%, 48%, 78%, and 56%, respectively. The LVET and HR did not change significantly, whereas the SI and CI decreased during anesthesia (29% and 26%, respectively). In conclusion, isoflurane produced direct effects on the Tei-index. The changes in systolic and diastolic parameters were supportive of this finding and were consistent with an overall impairment of left ventricular function during anesthesia.